2021
DOI: 10.34133/2021/9874273
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Electrostatic Interactions for Enhanced Conductivity in Metal-Organic Frameworks

Abstract: The poor electrical conductivity of metal-organic frameworks (MOFs) has been a stumbling block for its applications in many important fields. Therefore, exploring a simple and effective strategy to regulate the conductivity of MOFs is highly desired. Herein, anionic guest molecules are incorporated inside the pores of a cationic MOF (PFC-8), which increases its conductivity by five orders of magnitude while maintaining the original porosity. In contrast, the same operation in an isoreticular neutral framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The Zn–Zn distances between vertical and central Zn( ii ) ions are 3.06 Å and 3.14 Å, respectively, and the distances between vertical Zn( ii ) ions are 3.58 Å, showing no intermetallic bonding. Previous studies on zinc-pyrazolate coordination chemistry have found [Zn 4 O(pyz) 6 ] and [Zn 3 O(pyz) 3 ] clusters, and ZnN 4 tetrahedron SBUs; 18,39–41 yet to the best of our knowledge, the [Zn 9 O 2 (OH) 2 (pyz) 12 ] cluster has never been reported. The Zn 9 O 2 (OH) 2 cluster SBU is connected to twelve adjacent SBUs through Ni(salen)-based bis(pyrazolate) linkers to form a 3D network with face-centered cubic unit ( fcu ) topology, the same as that constructed from Ni 8 clusters and linear bis(pyrazolate) linkers.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The Zn–Zn distances between vertical and central Zn( ii ) ions are 3.06 Å and 3.14 Å, respectively, and the distances between vertical Zn( ii ) ions are 3.58 Å, showing no intermetallic bonding. Previous studies on zinc-pyrazolate coordination chemistry have found [Zn 4 O(pyz) 6 ] and [Zn 3 O(pyz) 3 ] clusters, and ZnN 4 tetrahedron SBUs; 18,39–41 yet to the best of our knowledge, the [Zn 9 O 2 (OH) 2 (pyz) 12 ] cluster has never been reported. The Zn 9 O 2 (OH) 2 cluster SBU is connected to twelve adjacent SBUs through Ni(salen)-based bis(pyrazolate) linkers to form a 3D network with face-centered cubic unit ( fcu ) topology, the same as that constructed from Ni 8 clusters and linear bis(pyrazolate) linkers.…”
mentioning
confidence: 79%
“…16 MOFs based on azolate donors usually show better stability than those of carboxylate donors because the sp 2 N atoms tend to adopt saturated coordination and thus become locally hydrophobic and unavailable for interaction with attacking reagents. 17,18 Meanwhile, interpenetrated motifs also significantly enhance the framework stability. 19 It is not only because interpenetrated networks could reduce the pore size and increase the wall thickness, but also due to the higher strength of noncovalent interactions in interpenetrated structures which lock the linkers in place and prevent their displacement.…”
mentioning
confidence: 99%
“…Precise design and prediction of MOFs with different topologies can be easily achieved through reticular chemistry methods [20][21][22][23][24]. MOFs are built from ligands and metal ions/clusters, which means that the structure of MOFs can be adjusted by implementing a molecular building block (MBB) approach to obtain targeted polynuclear rare earth (RE) metal clusters, and tuning the geometry, length, and functional groups of the ligands [25][26][27][28][29][30]. In other words, the design and prediction of MOFs and topologies can be reached by changing RE metal clusters and ligands with well-defined geometries [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…7,[71][72][73] Regularly, electrostatic interactions occur when Cl À interacts with positroncontaining groups such as guanidine or quaternary ammonium salts; hydrogen-bond interactions often occur between highly electronegative atoms and hydrogens along with luminescence shifting; Cl À -metal center stronger interactions are just mediated by coordination unsaturated metal centers (CUMSs) with Cl À . [74][75][76] Thus, in order to achieve available Cl À sensing, our tactics are simultaneously introduced uncoordinated N-and OHdual-sites to co-regulate hydrogen-bond interactions. Importantly, we can also fabricate CUMSs to further improve the Cl À sensing by effective designation of the LCMC structures.…”
Section: Introductionmentioning
confidence: 99%